2016
DOI: 10.9767/bcrec.11.2.542.161-169
|View full text |Cite
|
Sign up to set email alerts
|

Phy-chemical Attributes of Nano-scale V2O5/TiO2 Catalyst and Its’ Effect on Soot Oxidation

Abstract: The V2O5 catalysts which supported on nano-scale TiO2 with variation of vanadium contents (5%, 10%, 20% and 40%) were prepared by an incipient-wetness impregnation method. The phase structures of nano-scale V2O5/TiO2 catalysts with different loading rates were characterized by Scanning electron microscope (SEM), X-Ray diffraction (XRD) and Fourier transform infrared (FT-IR) spectra. The oxidation activities of catalysts over diesel soot were performed in a themogravimetric analysis (TGA) system. The kinetics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…23,31 Numerous pioneering reports highlighted the superior performance of TiV systems as composites VO x /TiO 2 or as doping compared to TiVO 4bimetal oxide on their plausible photocatalysis application. 32,33 Samdarshi et al (2010) evaluated the effect of silver on the titanium vanadium mixed metal (Ag/ TiV) oxides. 34 They observed that the system could absorb a large portion of the visible spectrum, where favourable electron transfer could be experienced anatase-rutile mixed phase where silver dominated through its scavenging action to reduce hole recombination.…”
Section: Introductionmentioning
confidence: 99%
“…23,31 Numerous pioneering reports highlighted the superior performance of TiV systems as composites VO x /TiO 2 or as doping compared to TiVO 4bimetal oxide on their plausible photocatalysis application. 32,33 Samdarshi et al (2010) evaluated the effect of silver on the titanium vanadium mixed metal (Ag/ TiV) oxides. 34 They observed that the system could absorb a large portion of the visible spectrum, where favourable electron transfer could be experienced anatase-rutile mixed phase where silver dominated through its scavenging action to reduce hole recombination.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of ZrO2 into TiO2 is able to increase the photocatalytic activity proven by 88.75 % degradation of MB at a ZrO2-TiO2 weight ratio of 1:1. Meanwhile, the V2O5 catalysts which supported on nano-scale TiO2 with variation of vanadium contents (5%, 10%, 20% and 40%) were studied by Mei et al [6]. The characterization results showed that the phase structure of V2O5 supported on TiO2 depends heavily on the vanadium contents, which will put great effects on the catalytic performances for soot oxidation.…”
mentioning
confidence: 99%
“…Another article focused on TiO2-based catalysts were conducted by Permadani et al [5] and Mei et al [6]. The composite of ZrO2-TiO2 produced from local zircon sand as a photocatalyst for the degradation of methylene blue in a single batik dye wastewater was studied by Permadani et al [5].…”
mentioning
confidence: 99%